Quantitative Analysis of Gene Expression During Calcium Homeostasis in E. coli - Arif, Muhammad; Tisa, Louis S (Bangladesh Journal of Microbiology, 2019)
Despite a wealth of knowledge regarding calcium’s role as secondary messenger in eukaryotic cells, relatively little is known about calcium homeostasis in bacteria. Our study employing molecular genetics and transcriptome analysis of calcium homeostasis previously exhibited a calcium regulation of gene expression in elevated or depleted calcium throughout E. coli genome. Here we report the results of our subsequent investigation into quantitative analysis using quantitative reverse transcriptase PCR (qRT-PCR) of gene expression in subsets of genes from wild-type and mutant strains with addition of calcium and chelation of calcium. Data from qRT-PCR reveal very high upregulation of genes yjeE and secA indicating their possible role as overactive calcium efflux systems in E. coli. Calcium is highly likely to be involved in stress response as evidenced by upregulation of marB in transposon mutants and by 10-fold induction of rpoS in elevated calcium condition in mutants defective in calcium transport. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 47-54